PENGEMBANGAN ALTERNASI PEMBELAJARAN PPKn MELALUI MODUL BERBASIS KECAKAPAN SOSIAL (SOCIAL SKILLS) - Zulis Mariastutik (Jurnal Pendidikan Pancasila dan Kewarganegaraan, 2015)
Abstract: In order to improve the quality and increase the understanding of material behavior as theimpact of learning on the Civic. More action to obtaining maximum result that is innovative teachingmaterials. Efforts to develop teaching materials made using this procedure Borg and Gall Researchand development. Product development is a substance produced by alternations Civics learningmodules based social skills (social skills), the material used is a matter of social norms , the characterthat was instilled religious values , living with others, honesty, discipline, and responsibility. Resultsof the study of social skills-based module products in design validation matter experts showed 84.37% and 97.91 % of the media show, both validators of creative and media experts show valid with therevised of product design. After the product have been revision, Product quality testing smallgroups of students, 89.58 % of the test group 89.84 % and a total of 89.7%. In interest of studentlearning trial on small groups of students 87 %, the big group total 89.4 % and all total 88.8%. Test thequality of the product is also done on the 97.5 % of the teacher. Based on the advice given by thematerial, the material produced using the curriculum in 2013.